2016
DOI: 10.1155/2016/4186089
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Factors Influencing Forest Harvesting in Smallholder Tobacco Production in Hurungwe District, Zimbabwe: An Application of Binary Logistic Regression Model

Abstract: Deforestation is one of the major effects posed by the smallholder tobacco farming as the farmers heavily depend on firewood sourced from natural forest for curing tobacco. The research aims at assessing the factors that influence the harvesting of natural forest in the production of tobacco. Data is collected through the structured questionnaire from 60 randomly selected farmers. Binary logistic regression model is used to explain the significance of factors influencing natural forest harvesting. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The study area has a mean annual rainfall of 750 to 1000 mm, concentrated between mid-November and the end of March (Anderson et al 1993). Soils vary from loamy sand to sandy clay loam soils under typical miombo woodland vegetation dominated by Brachystegia and Julbernardia species (Chivuraise et al 2016). Subsistence agriculture is the primary source of livelihood, with maize, groundnuts, cotton and tobacco as the major crops, and cattle, goats, and sheep as the major livestock (Ncube 2011).…”
Section: Study Areamentioning
confidence: 99%
“…The study area has a mean annual rainfall of 750 to 1000 mm, concentrated between mid-November and the end of March (Anderson et al 1993). Soils vary from loamy sand to sandy clay loam soils under typical miombo woodland vegetation dominated by Brachystegia and Julbernardia species (Chivuraise et al 2016). Subsistence agriculture is the primary source of livelihood, with maize, groundnuts, cotton and tobacco as the major crops, and cattle, goats, and sheep as the major livestock (Ncube 2011).…”
Section: Study Areamentioning
confidence: 99%
“…The logistic regression model is one of these techniques for empirical simulation. The logistic regression model has been used for studding different research problems such as forest coverage [ [45] , [46] , [47] ], urban development [ 8 , 43 ] and land use land cover change [ [48] , [49] , [50] ], predicting future trends in land use change [ 44 , 51 ] and urban sprawl [ [52] , [53] , [54] ]. Literatures revealed that logistic regression presents a clear picture of the weight of independent variables and their respective functions, as well as a good grasp of urban growth and urban growth processes (Aithal et al, 2017; Ramachandra et al, 2013 [ 55 , 56 ]; LRM allows and considers all socio-economic, physical, and demographic factors involved in the land use transformation and urban growth process, which are not available in many models and techniques [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…This wood is taken mainly from indigenous trees, resulting in deforestation, soil erosion, and biodiversity loss (Sacchetto, 2012;Madamombe et al, 2019) Soil degradation and deforestation have resulted from tobaccorelated farming practices in low and middle-income countries. (Chivuraise, 2011;Zvobgo and Tsoka, 2021;Kamuti, 2022). The increased demand for natural forest firewood used in tobacco curing has increased the rate of deforestation in Zimbabwe.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to most countries outside Africa, these produce flue-cured rather than naturally dried tobacco. As a result, there is a high rate of deforestation in natural forests from tobacco production(Chivuraise, 2011) According to WHO (2021), the major tobacco-growing countries in Africa are Zimbabwe, Zambia, Tanzania, Malawi, and Mozambique, as shown in Figure1. More than 70% of African…”
mentioning
confidence: 99%